Retail Betel Nut Sales Revenue in Wamena, Jayawijaya Regency - Rianik Thomas; Agus Sumaryadi; Tiomy B. Adi; Ester Wandik (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the income of retail Betel nut sellers in the city of Wamena, Jayawijaya Regency with a research time of 3 monthsThis type of research is descriptive research with a quantitative approach. The research sample used was 110 retail betel nut sellers, who came from the Potikelek, Jibama, Sinakma, Wouma markets and around Jl irian Wamena. The sample collection used was a saturated sample of the population and a sample of 110 betel nut sellers at the Wamena market point, Jayawijaya Regency. Collection Questionnaire data, observations, literature, data analysis techniques using score calculations. The analysis carried out is by using a quantitative approach by using the formula for calculating income variables with indicators of Total Revenue (TR) and Total Cost TC. The results showed that the acceptance of retail Betel nut sellers in Jayawijaya Regency per week averaged Rp. 1,457,141. The average cost per week is Rp. 268,960 and an average weekly income of Rp. 1,188,181